Forest management. Privatization issues - Żylicz, Tomasz (Journal of Public Governance, 2013)
The paper addresses management principles of the ‘State Forest Enterprise’ in Poland. The problem is a complex one, since the firm performs two important social functions. Firstly – as any enterprise – it provides employment and should balance its expenditures with financial revenues. Secondly – and this is why the ‘State Forest Enterprise’ is a unique firm – it stewards an important part of the national heritage which calls for an approach that departs from the logic characteristic for typical business projects. The duality of the ‘State Forest Enterprise’ casts serious doubts about its privatization attempts. On the one hand, privatization can enhance the efficiency of its operations. On the other hand, however, this would require a deep and direct involvement of the state budget in order to supply the public good that private foresters may choose not to provide.